2009
DOI: 10.1097/spc.0b013e3283311d09
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokines in cancer cachexia

Abstract: The main aim of the present review is to summarize and evaluate the different molecular mechanisms and catabolic mediators (mainly cytokines) involved in cancer cachexia since they may represent targets for future promising clinical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(105 citation statements)
references
References 57 publications
0
102
1
2
Order By: Relevance
“…The mechanisms, by which these cytokines influence the disease progression and outcome, are complex and multifactorial [43]. Importantly, it was shown that IL-1, TNF-α and IL-6 are responsible for development of symptoms, characteristic for cancer like anorexia, anemia, altered energy metabolism, weight loss, depression and fatigue and non-responsiveness to chemotherapy [43,[45][46][47]. Elevated IL-6 levels, present in the EOC serum and malignant ascites, were associated to residual disease after debulking and to disease recurrence [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms, by which these cytokines influence the disease progression and outcome, are complex and multifactorial [43]. Importantly, it was shown that IL-1, TNF-α and IL-6 are responsible for development of symptoms, characteristic for cancer like anorexia, anemia, altered energy metabolism, weight loss, depression and fatigue and non-responsiveness to chemotherapy [43,[45][46][47]. Elevated IL-6 levels, present in the EOC serum and malignant ascites, were associated to residual disease after debulking and to disease recurrence [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that the reason for such an increase might be related with the participation of PPARg and TNF-a as upstream mediators of haptoglobin production. Cancer cachexia induces a scenario with elevated levels of pro-inflammatory cytokines (Argiles et al 2009, including TNF-a, which in turn could inhibit PPARg expression and activity but stimulate haptoglobin expression. In this regard, increased levels of gene and protein expression of TNF-a in MEAT of Walker 256 tumour-bearing rats is well characterised (Machado et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increase in pro-inflammatory cytokine activity during cancer progression [24,25] , and systemic inflammation is a hallmark of cancer cachexia, indicated by the production of acute-phase response (APR) proteins such as C-reactive protein (CRP) and fibrinogen [26,27] . CRP is considered to be an accurate measure of the pro-inflammatory cytokine activity [28] that has been implicated in muscle wasting [29] .…”
Section: Inflammationmentioning
confidence: 99%